Knowledge and perspectives of the public towards the prevalence and harm associated with counterfeit medicines in Lebanon - Manale Noun; Layla Nasr; Iftikhar Khan; Basel Arafat; Sulaf Assi (Elsevier, 2021)
The Knowledge about the use of counterfeit medicines in Lebanon is still very limited. Thus, the objective of this study was to evaluate the degree of awareness of counterfeit medicines among the Lebanese population and the harm associated with their consumption. A cross-sectional study based on a questionnaire survey has been applied where a semi-structured survey questionnaire was distributed, between June 2017 and May 2018, among 750 participants from 98 Lebanese areas to assess their awareness regarding counterfeit medicines. Seven hundred and four participants completed the questionnaire. 55.4% purchased medicines regularly. The main sources of medicines were pharmacies (52.6%), government clinics (16.3%) and private clinics (8.7%). The most common purchased medicines were lifesaving ones (80%). In the majority of cases (71.9%), participants could not identify the manufacturer country. Overall, 46.2% of the participants were aware of counterfeit medicines. 5.4% of the participants experienced self-reporting adverse effects, among which 89.5% of cases were reported to pharmacists or other authorities. Despite the risk, 4.7% of participants were willing to buy a potential counterfeit medicine. In fact, 56. 4% of the participants associated low harm level with the use of counterfeit medicines. Despite their awareness of counterfeit drugs-associated risks, the majority of participants tend to buy them again. Informative public health campaign and health professionals training, to prevent counterfeit medicines-associated harms, should be implemented.